Green carbon dots derived from Zingiberis Rhizoma Carbonisatum alleviate ovalbumin-induced allergic rhinitis - Zhou, Long; Yang, Yingxin; Li, Tingjie; Zhao, Yafang; Yuan, Jinye; He, Chenxin; Huang, Yan; Ma, Jinyu; Zhang, Yue; Lu, Fang; Wu, Jiaze; Li, Zijian; et al. (Frontiers in Immunology, 2024)
BackgroundAllergic rhinitis (AR) affects up to 40% of the population, leading to significant healthcare expenditures. Current mainstream treatments, while effective, can lead to side effects and do not address the underlying immunological imbalances. Zingiberis Rhizoma Carbonisatum (ZRC), the partially charred product of Zingiberis Rhizoma (ZR), has been widely used clinically in China since ancient times to treat respiratory disorders.MethodsInspired by the similarity between high-temperature pyrolysis and carbonization processing of herbal medicine, ZRC derived CDs (ZRC-CDs) were extracted and purified through several procedures. Then, the physicochemical characteristics of CDs were delineated through a suite of characterization methods. Moreover, our investigation zeroed in on elucidating the ameliorative impacts of CDs on ovalbumin-induced rat models alongside their underlying mechanisms.ResultsZRC-CDs with particle sizes ranging from 1.0 to 3.5 nm and rich surface functional groups. Additionally, we observed that ZRC-CDs significantly attenuated nasal symptoms and pathological damage in ovalbumin-induced AR rats, and modulated lipid metabolism and type 2 inflammatory responses. They also inhibit PI3K/AKT and JAK/STAT pathways, which are associated with metabolism and inflammation. Importantly, ZRC-CDs demonstrated high biocompatibility, underscoring their potential as a novel therapeutic agent.ConclusionZRC-CDs offer a promising alternative for AR treatment and could help facilitate broader clinical use of the ZRC. In addition, the exploration of the inherent bioactivity of CDs can help to broaden their biological applications.